2018
DOI: 10.1016/j.surg.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The implications of insurance status on presentation, surgical management, and mortality among nonmetastatic breast cancer patients in Indiana

Abstract: To improve insurance-based disparities in Indiana, implementation of the Breast and Cervical Cancer Program in conjunction with expansion of insurance coverage to vulnerable low-income populations need to be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…19 Regarding survival rates according to healthcare coverage, previous studies have reported an association between worse outcomes and public medical insurance. 11,15,23,27,28,35,36 However, in our study, patients with public healthcare coverage did not have worse recurrence-free and overall survival than patients with private healthcare coverage. It could be argued that the absence of differences in survival between patients with private and public healthcare coverage may have been influenced by the fact that patients with Seguro Popular had access to the main treatment modalities as patients with private healthcare coverage at TecSalud; therefore, all patients were treated in a similar fashion, by the same group of healthcare professionals with equal infrastructure, regardless of medical coverage.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…19 Regarding survival rates according to healthcare coverage, previous studies have reported an association between worse outcomes and public medical insurance. 11,15,23,27,28,35,36 However, in our study, patients with public healthcare coverage did not have worse recurrence-free and overall survival than patients with private healthcare coverage. It could be argued that the absence of differences in survival between patients with private and public healthcare coverage may have been influenced by the fact that patients with Seguro Popular had access to the main treatment modalities as patients with private healthcare coverage at TecSalud; therefore, all patients were treated in a similar fashion, by the same group of healthcare professionals with equal infrastructure, regardless of medical coverage.…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, patients with public medical coverage had more advanced disease at diagnosis than those with private healthcare coverage, as described in other previous studies. 11 , 12 , 15 , 16 , 23 , 25 29 This could be explained by the high percentage of BC diagnoses made by self-detection (82.8% vs 47.9%, p < 0.001), rather than by screening mammography in patients with public healthcare coverage. A previous Mexican study identified that advanced BC stages at diagnosis are associated with diagnosis delay, which in turn is influenced by patients’ lack of BC awareness (dismissing symptoms as “not worrisome”), limited social network (the longer a patient conceals her symptoms from others, the longer she delays medical care), financial difficulties in seeking care (unable to justify taking medical leave from their jobs), as well as perception of medical errors in diagnostic impressions of the first doctors consulted.…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies have predominantly examined TTS from Medicare regional cancer registry populations, limiting their generalizability to commercially insured individuals. Significant differences in sociodemographic and clinical variables and outcomes, based on the type of insurance at presentation were identified by Obeng-Gyasi et al [14].…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, the uninsured, Medicaid-insured, those with low socioeconomic status (SES), and Black women continue to present with advanced stages of breast cancer and consequently have higher mortality rates than their privately insured, high-SES, and White female counterparts. 3,4 Possible drivers of these disparities include, but are not limited to, differences in access to and receipt of high-quality surgical care.…”
Section: Pastmentioning
confidence: 99%